Consumer behavior switching from human agents to chatbots in the health service industry - Yulianto, Dwi Fajar; Pratiwi, Titik; Irsan, Fatih Akbarul; Mustikasari, Faranita (Institute of Advanced Engineering and Science, 2025)
Artificial intelligence (AI) technology is used in organizations to replace human services with technology, altering customer service experiences. Only a limited number of studies have explored how consumers change their behavior from human-assisted to technology-assisted services when using AI in frontline and specialty healthcare services. This study examined the elements that impact consumers’ transition from human agents to AI-based conversational agents using the push-pull mooring framework. Data from 147 healthcare users was evaluated using structural equation modeling. The data indicates that push effects, specifically adaptability, have a negative impact on switching behavior, while pull effects, such as responsiveness and accessibility, have a positive impact on the switching behavior of customers.